THE ROLE OF “BELAJAR DARI RUMAH” EDUCATION PROGRAM BROADCASTED BY TVRI TO FOSTER STUDENTS’ LEARNING INTEREST AT GRADE VI SDN 02 NGETUK - Meila Noor Santi; Fina Fakhriyah; Lintang Kironoratri (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to determine the role of “Belajar dari Rumah” education program broadcasted by TVRI as well as the students’ motivation towards the program to foster students’ learning interest at grade VI SDN 02 Ngetuk. Learning interest refers to a high interest and tendency towards the process of seeking knowledge and honing skills through teaching, training, and experience. Education television is a television program that specifically broadcasts educational programs with the aim to provide students the learning resources in order to assist students in obtaining knowledge and moral contents. This study utilized descriptive qualitative method. The subjects of this study were 10 grade VI students at SDN 02 Ngetuk. Data were collected through interviews and questionnaires, and the data were analyzed through the process of data reduction, data presentation, and verification or drawing conclusions. The results showed that “Belajar dari Rumah” education program had three roles in learning, namely as a source of learning, a source of information, and a source of entertainment. Among the 10 informants, it was obtained that 30% of students used this program as a learning resource and showed a high learning interest, 20% of them used this program as a source of information and showed a moderate learning interest, and 50% of the students used this program as a source of entertainment and showed low learning interest. This indicated that the program did not significantly increase students’ learning interest.